Accruals Management and the Financial Performance of Listed Manufacturing Companies in Nigeria - Bababo, Aladetan Olumide; Christopher, Ebere Chukwuma (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This research paper investigated the relationship between accruals management and the financial performance of listed manufacturing companies in Nigeria. In order to achieve the aim of the research, six specific objectives and hypothesis were proposed. Accruals management was measured by discretionary accruals (DACC) and non-discretionary accruals (NDAC) while financial performance was measured by return on assets (ROA); net profit margin (NPM); and return on capital employed (ROCE). Data for the research covered a period of 11 years from 2010 to 2020 for 20listed manufacturing companies - thus comprising 220) firm years. Analytical employed for the purpose of the research included descriptive statistics, Pearson correlation and panel least square (PLS) regression method as well as ADF unit root test. Findings of the research revealed that there is a negative non-significant relationship between discretionary accruals and return on assets; net profit margin; and return on capital employed. And non-significant negative relationship between non-discretionary accruals and return on assets; net profit margin; and return on capital employed. From the findings, it was concluded that both discretionary and non-discretionary accruals do not make meaningful contribution to financial performance. It is further concluded that the ability to control/manage the flow of accruals is very important to corporate organisations. The researcher thus recommended that manufacturing companies take more interest in controlling/managing their accruals. This is because accrual in its uncontrolled/unmanaged form (non-discretionary accruals) is clearly shown to be harmful to the organisation. Secondly, not only should action be taken to manage accruals, it is important that such decisions are made with a clear achievable objective like building up liquidity in organisation, shoring finances or providing incentives to stakeholders.